PENGARUH PENDIDIKAN PEMUSTAKA (USER EDUCATION) TERHADAP PEMANFAATAN PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI IMAM BONJOL PADANG - Junira, Mai Dona; Ardoni, Ardoni (Scinary, 2023)
This study aims to describe: (1) how user education (user education) in the library of the Islamic State Islamic University Imam Bonjol Padang, (2) how the use of the library in the library of the Islamic State Islamic University Imam Bonjol Padang, and (3) how the influence of user education (user education) on the use of the library of the State Islamic University of Imam Bonjol Padang. This study uses a descriptive type of research using quantitative methods through the distribution of questionnaires as a data source. The population in this study were students of the Islamic State University of Imam Bonjol Padang with the determination of the sample through simple random sampling technique which is a random sampling technique without regard to the existing strata in the population. The results of the research questionnaire that the author conducted are as follows: (1) user education at the library of the Islamic State Islamic University Imam Bonjol Padang is classified as high because it has an average of 4.08 which is in the interval range of 3.41-4.200 in the high category. , (2) the use of the library in the library of the Islamic State Islamic University of Imam Bonjol Padang is classified as high which has an average of 4.13 in the interval range of 3.41-4.20 in the high category, (3) there is a significant influence between user education with the use of the library at the Imam Bonjol Padang Islamic State University library, which is 0.687 in a scale range of 0.61-0.80, it is quite strong.